2022
DOI: 10.1158/1078-0432.ccr-22-0262
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and Volume-Limiting Late Toxicity of FLASH Radiotherapy in Cats with Squamous Cell Carcinoma of the Nasal Planum and in Mini Pigs

Abstract: Purpose: The FLASH effect is characterized by normal tissue sparing without compromising tumor control. Although demonstrated in various preclinical models, safe translation of FLASH-radiotherapy stands to benefit from larger vertebrate animal models. Based on prior results we designed a randomized phase III trial to investigate the FLASH effect in cat-patients with spontaneous tumors. In parallel, the sparing capacity of FLASH-RT was studied on mini-pigs using large field irradiation. Experimental Design: Cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…All those evaluations are necessary to critically evaluate its toxicity and efficacy under a more clinically relevant scenario. Dose–volume effects can also have an important impact on FLASH-RT ( 85 ). Furthermore, oxygen content can be crucial in the appearance of FLASH effect ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…All those evaluations are necessary to critically evaluate its toxicity and efficacy under a more clinically relevant scenario. Dose–volume effects can also have an important impact on FLASH-RT ( 85 ). Furthermore, oxygen content can be crucial in the appearance of FLASH effect ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Larger animals such as the mini pig, cat, and dog cancer patients have also been assessed using FLASH and CONV RT [ 16 , 59 , 60 , 61 ]. Following irradiation, early effects on skin toxicity as well as late fibrosis were evaluated in the mini pig.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Their data showed a dose-modifying factor of at least 20% for single fraction treatment in favor of FLASH for the protection of normal tissue and prevention of fibrosis as endpoints. However, late skin toxicity in a subsequent study with mini pigs was observed with increasing volume, including permanent hyperkeratosis and skin contracture [ 59 ].…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers have now been published confirming this effect for different pre-clinical models, and with different irradiation modalities such as electrons, protons or heavy ions [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Based on the (almost) exclusively positive results from pre-clinical studies, a first human patient was already treated using FLASH in 2019 at the University Hospital in Lausanne [11] , [12] , and some first clinical trials in cats (with electrons [13] , [14] ) and in humans (with high-energy protons [15] and electrons [16] ) have been pursued.…”
mentioning
confidence: 99%